Anti‐angiogenesis triggers exosomes release from endothelial cells to promote tumor vasculogenesis. Issue 1 (17th June 2019) - Zeng, Ye; Yao, Xinghong; Liu, Xiaoheng; He, Xueling; Li, Liang; Liu, Xiaojing; Yan, Zhiping; Wu, Jiang; Fu, Bingmei M.
ABSTRACT: Although anti‐angiogenic therapies (AATs) have some effects against multiple malignancies, they are limited by subsequent tumor vasculogenesis and progression. To investigate the mechanisms by which tumor vasculogenesis and progression following AATs, we transfected microRNA (miR)‐9 into human umbilical vein endothelial cells (HUVECs) to mimic the tumor‐associated endothelial cells in hepatocellular carcinoma and simulated the AATs in vitro and in vivo. We found that administration of the angiogenesis inhibitor vandetanib completely abolished miR‐9‐induced angiogenesis and promoted autophagy in HUVECs, but induced the release of vascular endothelial growth factor (VEGF)‐enriched exosomes. These VEGF‐enriched exosomes significantly promoted the formation of endothelial vessels and vasculogenic mimicry in hepatocellular carcinoma and its progression in mice. Anti‐autophagic therapy is proposed to improve the efficacy of AATs. However, similar effects by AATs were observed with the application of anti‐autophagy by 3‐methyladenine. Our results revealed that tumor vasculogenesis and progression after AATs and anti‐autophagic therapies were due to the cross‐talk between endothelial and tumor cells via VEGF‐enriched exosomes.